Cholinesterase inhibition activity and molecular docking study of eugenol derivatives - Khairunisa Mohd Zamli; Asnuzilawati Asari; Hanis Mohd Yusof; Nurul Huda Abdul Wahab; Kooi, Yeong Khaw; Vikneswaran Murugaiyah; al-Rashida, Mariya; Habsah Mohamad; Hasnah Osman (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study was conducted to explore the anticholinesterase inhibition property of eugenol derived molecules. Ten eugenol derivatives were synthesized and evaluated for the inhibitory activities against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) by Ellman’s method. Most of the tested derivatives showed higher inhibition on BChE than AChE, however, their overall inhibitory activity was weak. In contrast, three derivatives (compounds 3,6,9) showed higher and good AChE inhibitory activity of more than 50% inhibition at 10 µg/mL. Among them, compound 9 bearing a ethyl substituent at para position of the benzoyl ring showed the most potent AChE inhibition, with IC50 of 5.64 µg/mL. Ligand-protein docking simulation was also performed for the most active derived molecules (compounds 3,6,9).